Radioscapholunate Fusion for Radiocarpal Osteoarthritis: Prognostic Factors of Clinical and Radiographic Outcomes - Degeorge, Benjamin; Montoya-Faivre, David; Dap, François; Dautel, Gilles; Coulet, Bertrand; Chammas, Michel (Journal of Wrist Surgery, 2019)
Background Radioscapholunate (RSL) fusion is a surgical option to manage radiocarpal osteoarthritis. Many authors upgrade the procedure by adding distal scaphoid excision with or without excision of the triquetrum. Our objective was to identify the prognostic factors for good clinical and radiographic outcomes of RSL arthrodesis.Purpose Distal scaphoid excision improves both scaphotrapeziotrapezoidal osteoarthritis and radiocarpal fusion, and excision of the triquetrum is not critical to achieving satisfactory outcomes.Methods In this retrospective and bicentric investigation, all wrists were managed with RSL fusion for posttraumatic radiocarpal osteoarthritis. A total of 85 patients were included and evaluated at the revision by clinical (pain, wrist motion, and strength), functional (Disabilities of the Arm, Shoulder, and Hand questionnaire, Patient-Related Wrist Evaluation score, and Modified Mayo Wrist Score), and radiological (scaphotrapeziotrapezoidal, midcarpal osteoarthritis, and radiocarpal nonunion) examinations. We assessed prognostic factors for clinical and radiographic (osteoarthritis and nonunions) outcomes.Results The average follow-up was 9.1 years (1–21.4). Work-related accidents adversely impacted the clinical outcomes, and distal scaphoid excision significantly improved them and decreased scaphotrapeziotrapezoidal osteoarthritis and nonunion. Neither distal scaphoid excision nor excision of the triquetrum influenced midcarpal osteoarthritis. Radiocarpal fusion was significantly promoted by memory staples and bone grafting.Discussion Distal scaphoid excision should be preferred to improve the functional results while decreasing scaphotrapeziotrapezoidal osteoarthritis and radiocarpal nonunion rates. Excision of the triquetrum appears to be an alternative to radioulnar resection–arthroplasty to solve ulnocarpal impaction syndrome. Strict surgical procedure must be observed to promote RSL fusion combining solid bone fixation and the use of bone graft.Level of evidence This is a level IV, case series, retrospective series.
Keywords: arthrodesis; fusion; radioscapholunate; radiocarpal; arthritis; prognostic factor